The role of positron emission tomography-computed tomography and magnetic resonance imaging in diagnosis and follow up of multiple myeloma - Caers, Jo; Withofs, Nadia; Hillengaß, Jens; Simoni, Paolo; Zamagni, Elena; Hustinx, Roland; Beguin, Yves (Haematologica, 2014)
Multiple myeloma is the second most common hematologic malignancy and occurs most commonly in elderly patients. Almost all multiple myeloma patients develop bone lesions in the course of their disease or have evidence of bone loss at initial diagnosis. Whole-body conventional radiography remains the gold standard in the diagnostic evaluation, but computed tomography, magnetic resonance imaging and 18F-fluorodeoxyglucose positron emission tomography are increasingly used as complementary techniques in the detection of bone lesions. Moreover, the number of lesions detected and the presence of extramedullary disease give strong prognostic information. These new techniques may help to assess treatment response in solitary plasmacytoma or in multiple myeloma. In this article, we review recent data on the different imaging techniques used at diagnosis and in the assessment of treatment response, and discuss some current issues.